A formative study of weekly iron-folic Acid (WIFA) supplementation for adolescent school girls in West Java Indonesia. - Ali Khomsan; Riyadi, Hadi; Ekawidyani, Karina Rahmadia; Dina, Resa Ana; Nurhidayati, Vieta Annisa; Prasetya, Guntari (Nutrición Clínica y Dietética Hospitalaria, 2025)
Introduction: The WIFA (Weekly Iron-Folic Acid) supplementation program for school adolescent girls is mainly allocated in regencies where they are found as locusts of stunting. Adolescence presents a second window of opportunity for establishing healthy lifelong nutrition. The objectives of this study were to assess the performance of WIFA supplementation for school adolescent girls in West Java Indonesia. Methods: This study used a cross-sectional design. The study was conducted for 3 months in five high schools in Tasikmalaya and five high schools in Ciamis, West Java Province, Indonesia. Systematic random sampling was used to select the school adolescent girls with their mothers using random numbers generated for each class using school girl attendance register. The total subjects were 280 school adolescent girls. Results: There were only 64.1% of school adolescent girls who consumed WIFA tablets. The average number of WIFA tablets received by school adolescent girls was only 18 tablets per year, while it should be 52 tablets. School adolescent girls experienced many side effect during IFA consumption and it made them resist to consume it. Many students (55.6%) stated that there was no benefit of consuming IFA tablets. Conclusion: Lack of understanding about anemia among school adolescent girls and less optimal of WIFA management might have been responsible on adherence of consuming WIFA tablets. It indicated that nutrition education for school adolescent girls and the WIFA program implementation should be improved.